Rebirth, Devastation and Sickness: Analyzing the Role of Metaphor in Media Discourses of Nuclear Power. Issue 5 (3rd September 2017) - Renzi, Barbara Gabriella; Cotton, Matthew; Napolitano, Giulio; Barkemeyer, Ralf
ABSTRACT: Nuclear power plays an important but controversial role in policies to ensure domestic energy security, fuel poverty reduction and the mitigation of climate change. Our article construes the problem of nuclear power in terms of social discourse, language and public choice; specifically examining the role that metaphors play in the policy domain. We empirically analyze metaphors as framing devices in nuclear energy policy debates in the UK between April 2009 and March 2013, thereby capturing the impact of the Fukushima nuclear disaster in 2011. We employ documentary analysis of major UK national broadsheet and tabloid newspapers, using electronic bibliographic tools to extract the metaphors. We then map these metaphors using a Type Hierarchy Analysis, which examines how elements of the target domain (energy technologies and policies) originate from a different source domain. Type hierarchies identify and categorize metaphors, defining the affectual and emotional responses associated with them, providing us with grounded insight into their role in shaping discourse and as a consequence influence public engagement with energy policy. Our analysis highlights three emergent domains of discourse metaphors and discusses the implications of their deployment. Metaphors were found to be classified into three different categories: Rebirth ( Renaissance ), Devastation ( Apocalypse, Inferno, Genie and Bomb ) and Sickness ( Addiction and Smoking ).